Tarsier Anterior Chamber Cell Grading: Improving the SUN Grading Scheme with a Visual Analog Scale. (17th November 2022) - de Smet, Marc D.; Haim-Langford, Daphne; Neumann, Ron; Kramer, Michal; Cunningham, Emmett; Deutsch, Lisa; Milman, Zohar
ABSTRACT: Purpose: To compare an analog visual scale in grading anterior chamber cells (ACC) to a modified Standardization of Uveitis Nomenclature (SUN) ACC scale. Method: A graphical representation of anterior chamber cells as a reference and a test set was created and shown to two groups of experienced uveitis experts. Group 1 was given the analog scale in written format, while group two was given the reference images for comparison. Each test subject was asked to provide the best approximation for each grade. Results: Eleven graders participated in phase 1. Correct grading occurred in 87.4% of cases. Discrepancies were seen at all grades. Only 3 of 11 graders were able to achieve a perfect score. Seven graders participated in phase 2. Agreement was 95.2% with 4/7 graders achieving a perfect score. Discrepancies were seen at higher grades only. Conclusions: ACC grading is improved by a visual grading scale, and interobserver variability is reduced.